Synthesis and atomic scale characterization of Er2O3 nanoparticles: enhancement of magnetic properties and changes in the local structure. (22nd March 2018) - Corrêa, Eduardo L; Bosch-Santos, Brianna; Freitas, Rafael S; da Penha A Potiens, Maria; Saiki, Mitiko; Carbonari, Artur W
Abstract: In the investigation reported in this paper a modified thermal decomposition method was developed to produce very small Er2 O3 nanoparticles (NPs). Particles structure, shape and size were characterized by x-ray diffraction and transmission electron microscopy which showed that the synthesis by thermal decomposition under O2 atmosphere produced very small and monodisperse NPs, allowing the investigation of finite-size and surface effects. Results of magnetization measurements showed that the smallest particles present the highest values of susceptibility that decrease as particle size increases. Specific heat measurements indicate that the sample with the smallest NPs (diameter ∼5 nm) has a Néel temperature of 0.54 K. The local structure of particles was investigated by measurements of hyperfine interactions with perturbed angular correlation spectroscopy using 111 Cd as probe nuclei replacing the cationic sites. Results showed that the relative population of sites 8b increases in both the core and surface layer of particles.